Conflicting language ideologies in choral singing in Trinidad. (January 2017) - Wilson, Guyanne
Abstract: This article investigates language ideologies and attitudes in Trinidad by looking at the context of choral singing. It is based on data that was collected through questionnaires, interviews, and observations with choral conductors, singers, and audiences. It reports that a standard language ideology that favours British English exists in this context, though the local variety of Standard English also enjoys considerable prestige. The local Creole is highly stigmatized, contrary to earlier work that claimed that it enjoyed increased prestige. The study concludes that language ideologies are not uniform within Trinidad, can evolve, and are context dependent. Highlights: Standard British English accents enjoy prestige in classical choral singing. Trinidadian Standard English features are widely used and accepted. Trinidad English Creole accents are avoided, except when singing local songs. Stakeholders have conflicting beliefs about language use in choral singing. A classical choral singing style exists and is independent of regional dialects.